Caspase Inhibitors Attenuate Superantigen-Induced Inflammatory Cytokines, Chemokines, and T-Cell Proliferation - Krakauer, Teresa (American Society for Microbiology, 2004)
Proinflammatory cytokines mediate the toxic effect of superantigenic staphylococcal exotoxins (SE). A pan-caspase inhibitor suppressed SE-stimulated T-cell proliferation and the production of cytokines and chemokines by human peripheral blood mononuclear cells. These data suggest that caspase inhibitors may represent a novel therapeutic modality for treating SE-induced toxic shock.